2021
DOI: 10.1177/20563051211047667
|View full text |Cite
|
Sign up to set email alerts
|

The Sociomateriality of Rating and Ranking Devices on Social Media: A Case Study of Reddit’s Voting Practices

Abstract: Rating and ranking devices are everywhere on social media. While these devices may seem like objective tools to measure value and rank content, research shows how they profoundly shape social interaction and emotional expression and are central to platform moderation. Yet, very little is known about how users themselves talk about these devices, much less what this can tell us about how these devices co-constitute social reality on platforms. To explore this gap, we examine Reddit’s rating and ranking device, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In a press release detailing certain aspects of how the FYP functions, TikTok (2020a, p. 1) notes that users watching a video in its entirety before scrolling down was a 'strong indicator of interest' that would lead to higher ranks and more likely to be recommended. This supports Damoyee's assertion and aligns with previous research on the role of user practices in participatory ranking systems (Graham & Rodriguez, 2021).…”
Section: Tiktok Creators and Visibility Moderationsupporting
confidence: 90%
See 1 more Smart Citation
“…In a press release detailing certain aspects of how the FYP functions, TikTok (2020a, p. 1) notes that users watching a video in its entirety before scrolling down was a 'strong indicator of interest' that would lead to higher ranks and more likely to be recommended. This supports Damoyee's assertion and aligns with previous research on the role of user practices in participatory ranking systems (Graham & Rodriguez, 2021).…”
Section: Tiktok Creators and Visibility Moderationsupporting
confidence: 90%
“…On the microlevel, visibility moderation can also be exemplified by content creators and users’ collective curation of comments. Through features such as ‘like’, ‘dislike’, ‘upvote’ or ‘downvote’, the practises of participatory ranking and curation of user‐generated content are widely implemented on social media (Graham & Rodriguez, 2021; Massanari, 2017). On TikTok, video creators can directly moderate their comments and viewers participate in ranking comments through interaction.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Our results suggest that YouTube's comments feature can, like anonymous message boards such as 4chan and 8kun, function as an under-regulated epistemic space in which conspiracy theories flourish. Research on Reddit has established the important role of user comments to social processes of knowledge production on platforms, particularly for judgments on information value and credibility (Graham & Rodriguez, 2021). Sundar's (2008) study of technology effects on credibility found that "when users were attributed as the source of online news, study participants liked the stories more and perceived them to be of higher quality than when news editors or receivers themselves were identified as sources" (p. 83).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we found short conspiratorial statements receive the most engagement (RQ1b), and machine learning text classifiers typically perform poorly on short, ambiguous text inputs (Huang et al, 2013). On Reddit, such a comment might be recognised for the discursive tactic that it is and thereby moderated in a variety of ways, for example: downvoted by other users until it is hidden automatically from view (Graham & Rodriguez, 2021); flagged as "controversial" and de-ranked in terms of visibility; removed by volunteer subreddit moderators; or simply not allowed because the user does not have the minimum credibility ("karma" score) to post comments in that particular subreddit. In severe cases where community-led moderation fails, Reddit may "quarantine" or even ban entire subreddits that become overrun with misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…Cheney-Lippold (2011), on the other hand, speaks of the "soft power" of algorithms to refer to their influence on the existential possibilities of individuals. Many empirical pieces of research highlight the authority of algorithms in the fields in which they are applied (Haimson et al, 2021;Graham & Rodriguez, 2021;Gorwa et al, 2020;Campbell-Verduyn et al, 2017). Among these, we can mention Ma and Kou (2021) research in which emerges that the algorithm underlying the moderation of YouTube's content can orient not only the individual and collective action of YouTubers but also their feelings of insecurity and precariousness.…”
Section: Emerging Features Of Socio-digital Objectsmentioning
confidence: 99%